Establishment and characterization of a stable hERG cell line for high-throughput drug cardiac safety screening - Lu, Hailin; Guo, Qingqing; Qiu, Qinling; Hu, Jiying (浪淘沙预印本平台, 2025)
The human Ether-a-go-go Related Gene (hERG)-encoded potassium channel is critical for cardiac ventricular action potential repolarization and serves as a core target for preclinical drug safety screening. The lack of stable, high-expression hERG cell models has limited the reliability and throughput of functional assays for hERG channel evaluation. Thus, developing a robust stable hERG-expressing cell line is essential for advancing high-throughput drug safety assessments.A stable HEK293T cell line with high-level HA-tagged hERG expression was established in this study. The hERG gene was subcloned into a lentiviral vector where EGFP was linked to hERG via a P2A self-cleaving peptide. EGFP-positive cells were isolated by flow cytometry (FACS) to generate monoclonal cell lines. Confocal microscopy was used to validate hERG expression and sub-cellular localization. Electrophysiological functionality was assessed via manual patch-clamp, and high-throughput performance was verified using the SyncroPatch 384i automated patch-clamp (APC) system. The sensitivity of the cell line to the hERG-specific blocker E4031 was evaluated to confirm its utility for drug screening. FACS analysis confirmed robust EGFP positivity in the stable cell line. Confocal imaging demonstrated co-localization of HA-tagged hERG and EGFP signals, with hERG predominantly localized to the cell membrane. Manual patch-clamp recordings revealed canonical hERG current properties. APC-based current profiling showed 100% of blank 293T cells (n=48) had currents 50 pA (87% >100 pA), with 13.9% (n=30) at 100-200 pA, 23.6% (n=51) at 200-400 pA, 20.8% (n=45) at 400-600 pA, and 28.7% (n=62) >600 pA. Pharmacological validation with E4031 revealed a concentration-dependent inhibition of hERG currents, with a half-maximal inhibitory concentration (IC₅₀) of 29.8 nM-consistent with values reported in the literature.The stable hERG-expressing HEK293T cell line developed herein exhibits consistent hERG expression, channel function, and physiological sensitivity to hERG blockers. When combined with high-throughput APC systems, this cell model provides a robust, standardized platform for preclinical evaluation of drug-induced hERG inhibition, facilitating early identification of diLQTS risks and supporting the development of safer pharmaceutical candidates.